2022
DOI: 10.3390/polym14204278
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Polyesters: Study of Variations in Their Morphological and Thermal Properties through Changes in Composition of Alkyl-Substituted (ε-DL) and Non-Substituted (ε-CL, EB, L-LA) Monomers

Abstract: Three series of polyesters based on monomer combinations of ε-caprolactone (ε-CL), ethylene brassylate (EB), and l-Lactide (LLA) with the alkyl substituted lactone ε-decalactone (ε-DL) were synthesized at different molar ratios. Copolymers were obtained via ring opening polymerization (ROP) employing TBD (1,5,7-triazabicyclo-[4.4.0]-dec-5-ene), an organic catalyst which can be handled under normal conditions, avoiding the use of glove box equipment. The molar monomer composition of resulting copolymers differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…(Figure S13) Interestingly, no melting peak was observed for Cu-THPP-PDLLA synthesized from the ROP of L - lactide. Similar results have been reported by López-González and co-workers . They found the amorphous feature of the polymer when using L -lactide monomer and TBD catalyst, suggesting the detrimental effect of TBD on the crystallinity of PLLA.…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(Figure S13) Interestingly, no melting peak was observed for Cu-THPP-PDLLA synthesized from the ROP of L - lactide. Similar results have been reported by López-González and co-workers . They found the amorphous feature of the polymer when using L -lactide monomer and TBD catalyst, suggesting the detrimental effect of TBD on the crystallinity of PLLA.…”
Section: Results and Discussionsupporting
confidence: 89%
“…Similar results have been reported by Loṕez-Gonzaĺez and co-workers. 32 They found the amorphous feature of the polymer when using L-lactide monomer and TBD catalyst, suggesting the detrimental effect of TBD on the crystallinity of PLLA. Moins et al also reported that the polyester obtained using TBD as an achiral catalyst led to the loss of the polymer crystallinity during the polymerization at 70 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%